Pottery from Roman Malta - Anastasi, Maxine, 1986- (Malta archaeological review supplement ;, 2019)
A comprehensive study of Maltese pottery forms from key stratified deposits spanning the 1st century BC to mid-4th century AD. Ceramic material is analysed and quantified in a bid to understand Maltese pottery production during the Roman period.